Amorphous Iron Phosphate: Inorganic Sol-Gel Synthesis-Sodium and Potassium Insertion - Fatima-Ezzahra Maarouf; Sanaa Saoiabi; Khalil Azzaoui; Hind Khalil; Mariam Khalil; Ahmed El Yahyaoui; Ahmed Saoiabi; Belkheir Hammouti; Moulay Hfid Youssoufi; Sergey Shityakov; Othman Hamed; Shehdeh Jodeh; Rachid Sabbahi (Universitas Pendidikan Indonesia, 2022)
Amorphous iron phosphate, FePO4.2H2O, was synthesized at ambient temperature using an inorganic sol-gel method coupled with a microwave route. The experimental conditions for the gelling of the Fe (III)-H3PO4 system are defined. Potentiometric Time Titration (PTT) and Potentiometric Mass Titration (PMT) methods were used to investigate the acid-base surface chemistry of obtained phosphate. Variations of surface charge with the contact time, Q = f(t), are examined for time contact ranged from 0 to 72 hours. The concentrations suspensions used for this purpose were 0.75, 1.25, and 2.5 g/L. The point of zero charges (PZC) and isoelectric point (IEP) were defined using the derivative method examining the variations , at lower contact time. A value of 5.4 was obtained for both PZC and IEP. Q in the function of the t method is performed for synthesized FePO4. 2H2O in NaCl and KCl electrolytes. The optimal surface charge of 40 C corresponding to insertion of 4.2x10-4 M of Na+ or K+, is achieved in explored conditions. The results suggest that the synthesized iron phosphate is amorphous.